Immunization status and childhood morbidities as determinants of PEM among under-five children in slums of Kanpur - Agarwal, Neha; Sharma, Ram Pravesh; Chandra, Suresh; Varma, Punit; Midha, Tanu; Nigam, Seema (Indian Journal of Community Health, 2014)
Introduction: Childhood morbidities like Acute Respiratory Infections (ARI), diarrhoea and malnutrition are very common. As per NFHS-3, only 23% children aged 12-23 months were fully immunized in Uttar Pradesh. 9% under-five children had diarrhoea and 7.1% had ARI. Objective: To assess the impact of immunization status and childhood morbidities on nutritional status of under five children. Material & Methods: A cross sectional study was carried out among under five children in slums of Kanpur, using 30 cluster sampling technique. The sample size was calculated to be 375. From each slum, 13 subjects were studied thus giving a total sample size of 390. A pre-designed and pre-tested questionnaire was used to illicit the requisite information from the mothers of study subjects. Weight was recorded using standard technique for the same. Protein Energy Malnutrition (PEM) was graded using IAP classification. Analysis of data was done using percentages and Chi square test. Results: The overall prevalence of PEM was found to be 54.87%. Malnutrition was found to be significantly higher (69.23%) among unimmunized study subjects (p?0.05). Among children who reported episodes of ARI and diarrhoea within last 1 month, 67.86% and 78.52% subjects respectively were malnourished. The association between PEM and these childhood morbidities was found to be statistically significant (p?0.05). Conclusion: Prevention of diarrhoea and ARI and complete immunization of children under five years of age through National programmes and other health measures is the need of the hour for combating malnutrition in under five.